2018
DOI: 10.1021/acsami.8b05428
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Facilitated Comprehensive Analysis of Cellular Nucleic Acid Binding Proteins for Lung Cancer

Abstract: Nucleic acid binding proteins (NABPs) mediate a broad range of essential cellular functions. However, it is very challenging to comprehensively extract whole cellular NABPs due to the lack of approaches with high efficiency. To this end, carbon nanomaterials, including graphene oxide (GO), carboxylated graphene (cG), and carboxylated carbon nanotube (cCNT), were utilized to extract cellular NABPs in this study through a new strategy. Our data demonstrated that GO, cG, and cCNT could extract nearly 100% cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…One study found that SAMHD1 is down regulated in lung cancer by methylation and inhibits tumour cell proliferation . The other study reported that SAMHD1 levels increase in the serum of lung cancer patients upon progression [Shang et al, 2018]. Our analysis of SAMHD1 data found significantly higher 5-year survival rates in patients with tumours displaying high SAMHD1 expression levels (Supplementary Table 1) supporting the first study.…”
Section: Literature Review Samhd1 and Cancersupporting
confidence: 85%
See 2 more Smart Citations
“…One study found that SAMHD1 is down regulated in lung cancer by methylation and inhibits tumour cell proliferation . The other study reported that SAMHD1 levels increase in the serum of lung cancer patients upon progression [Shang et al, 2018]. Our analysis of SAMHD1 data found significantly higher 5-year survival rates in patients with tumours displaying high SAMHD1 expression levels (Supplementary Table 1) supporting the first study.…”
Section: Literature Review Samhd1 and Cancersupporting
confidence: 85%
“…Among the 35 articles that reported on an association between SAMHD1 and cancer, four did not (entirely) support the ‘SAMHD1 is a tumour suppressor’ narrative [Yang et al, 2017; Kodigepalli et al, 2018; Shang et al, 2018; Xagoraris et al, 2021]. One study correlated high SAMHD1 levels with metastasis formation in colorectal cancer [Yang et al, 2017].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Filter‐aided sample preparation digestion was carried out for protein digestion as previously described . Obtained peptides for LC‐MS/MS analysis was performed using an automated platform consisting of an EASY‐nLC 1000 LC system (Thermo Fisher Scientific) coupled to LTQ‐Orbitrap XL Hybrid mass spectrometer (Thermo Fisher Scientific) equipped with a nano‐ESI ion source setup.…”
Section: Methodsmentioning
confidence: 99%
“…Widely expressed in several tissues, SAMHD1 mutations have also been detected in breast cancer, myeloma, pancreatic cancer and others. The mutation and modification sites of SAMHD1 in different types of cancer are presented in Tables I (99)(100)(101)(102)(103)(104) and II, respectively.…”
Section: Role Of Samhd1 In Tumorigenesis and Cancer Treatmentmentioning
confidence: 99%